Sustaining Community Violence Intervention and Prevention (CVI): A State Readiness Assessment for Funding CVI Through Medicaid. - Strange, Catherine Clare; Pugliese, Katheryne; Ranjan, Sheetal; Shah, Aakash (Inquiry (00469580), 2025)
Community violence intervention and prevention (CVI) programs aim to reduce gun violence and its associated harms through community-driven strategies. Programs' long-term sustainability is challenged by inconsistent and insufficient funding, however, which can be detrimental to the individuals who depend on these services as they navigate recovery from a violent injury. As states explore new funding mechanisms, Medicaid reimbursement has emerged as a viable option, however little implementation guidance exists specific to this policy option in the CVI context. This study combines the implementation science and public health infrastructure literatures with data from a recent multistate case study (n = 17 key stakeholder interviews) to produce a readiness assessment for funding CVI through Medicaid. The readiness assessment is organized by the stages of the EPIS (Exploration-Preparation-Implementation-Sustainment) framework and provides tangible guidance to states looking to improve their CVI infrastructure. The assessment includes recommendations that reflect key challenges and facilitators of implementation, as dictated by those who have recently navigated this process. Given the urgency of reducing gun violence and its harms, this study underscores the importance of structured policy planning to enhance CVI program viability and sustainability. This study contributes to the growing implementation science and public health infrastructure literatures by offering a theoretically grounded and evidence-informed tool to support policymakers in establishing sustainable funding mechanisms for CVI.